PENGEMBANGAN BAHAN AJAR ELEKTRONIK BERBASIS LITERASI MATEMATIS UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Muhammad Toha Anshori; Dede Suratman; Bistari Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstract This study aims to describe the development of electronic teaching materials based on mathematical literacy on trigonometry material and students' mathematical communication skills in class X TKJ SMK Negeri 4 Pontianak.. From the research results, the development of teaching materials based on mathematical literacy has been validated by two validators and tested so that the teaching materials that have been made are suitable for use. Mathematical communication skills can be seen from the test results which refer to the indicators of mathematical communication. The mean score of 9 students who worked on the questions based on each indicator was to state the situation of daily events in a mathematical model and to solve it an average score of 10; compile a mathematical model of everyday events about trigonometry and solve it an average score of 10; depicting or presenting real objects, pictures and diagrams in the form of mathematical ideas and or symbols with an average score of 8.89; explain ideas, situations and mathematical relations, orally and in writing using real objects, and algebraic expressions with an average score of 4.78; restating a drawing or description or a paragraph of mathematics in one's own language an average score of 7.44. Keywords: Mathematical Communication, Mathematical Literacy, Teaching Materials